Studies on curcumin fortification in different lassi types using Tween-80 as a binding material - Maurya, Nripendra; Khamrui, Kaushik; Prasad, Writdhama G (Indian Journal of Dairy Science, 2020)
The present study was undertaken to prepare curcumin fortified lassi, a dairy based fermented beverage. Tween-80 was used as a binding agent for curcumin. Curcumin was fortified at different curcumin: Tween-80 ratio. Increasing curcumin: Tween-80 ratio decreased the curcumin retention, and decreasing the ratio affected the sensory properties of the sample. Optimum curcumin: Tween-80 was found to be 1:5 and was employed in salted and sweet lassi for selection of suitable lassi variant for curcumin fortification. At the optimized ratio, sweet lassi was found to be a sensorially better delivery system for curcumin as compared to salted lassi. Curcumin retention remained unaffected in both the lassi types.